2013
DOI: 10.1007/s00572-013-0527-6
|View full text |Cite
|
Sign up to set email alerts
|

The arbuscular mycorrhizal symbiosis attenuates symptom severity and reduces virus concentration in tomato infected by Tomato yellow leaf curl Sardinia virus (TYLCSV)

Abstract: The arbuscular mycorrhizal (AM) symbiosis is considered a natural instrument to improve plant health and productivity since mycorrhizal plants often show higher tolerance to abiotic and biotic stresses. However, the impact of the AM symbiosis on infection by viral pathogens is still largely uncertain and little explored. In the present study, tomato plants were grown under controlled conditions and inoculated with the AM fungus Funneliformis mosseae. Once the mycorrhizal colonization had developed, plants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 61 publications
3
38
0
1
Order By: Relevance
“…This discrepancy may be related to the various characteristics of potato cultivars used in both experiments (tolerant vs. sensitive), since virus behavior may differ depending on the host genotype (Valkonen, 2015;Davie et al, 2017). Nevertheless, the investigation by Maffei et al (2014), examining different experimental biosystem consisting of tomato, Tomato yellow leaf curl Sardinia virus (TYLCSV) and Funneliformis mosseae, indicated attenuation of viral disease symptoms upon symbiosis. More recently, Wang et al (2018) showed that mycorrhization of tomato affected by Cladosporium fulvum (pathogenic mold) caused significant increase in activities of both superoxide dismutase and peroxidase, which correlated with decrease in H 2 O 2 level.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be related to the various characteristics of potato cultivars used in both experiments (tolerant vs. sensitive), since virus behavior may differ depending on the host genotype (Valkonen, 2015;Davie et al, 2017). Nevertheless, the investigation by Maffei et al (2014), examining different experimental biosystem consisting of tomato, Tomato yellow leaf curl Sardinia virus (TYLCSV) and Funneliformis mosseae, indicated attenuation of viral disease symptoms upon symbiosis. More recently, Wang et al (2018) showed that mycorrhization of tomato affected by Cladosporium fulvum (pathogenic mold) caused significant increase in activities of both superoxide dismutase and peroxidase, which correlated with decrease in H 2 O 2 level.…”
Section: Discussionmentioning
confidence: 99%
“…Mycorrhizal associations benefit not only plant nutrient absorption ( Smith and Read, 2008 ), but also plant resistance to diverse abiotic stresses ( Ruiz-Lozano et al, 1996 ) and soil-borne fungal pathogens ( Harrier and Watson, 2004 ; Bi et al, 2007 ). More interestingly, AM symbiosis also enhances plant resistance against foliar pathogens such as fungal pathogens [e.g., Botrytis cinerea ( Pozo et al, 2010 ; Fiorilli et al, 2011 ) and A. solani ( Fritz et al, 2006 )], bacteria [e.g., Xamantomonas campestris ( Liu et al, 2007 ) and viruses (e.g., Tomato yellow leaf curl Sardinia virus ( Maffei et al, 2014 )].…”
Section: Discussionmentioning
confidence: 99%
“…(MUCL 43204), Claroideoglomus claroideum (BEG 23) and Funelliformis mosseae (BEG 12) had an intermediate level of colonization, confirming that tomato is intermediate in mycorrhizal dependency [28]. It is known that AM symbiosis could enhance plant resistance against a wide range of viral, bacterial and fungal pathogens [10,12,21,23,38], but our report is the only one regarding the bacterial disease caused by Cmm. The present study showed that Ri induced the most effective systemic resistance against Cmm among seven AMF isolates tested.…”
Section: Discussionmentioning
confidence: 55%